Covid-19 and the Clash of Narratives: From Cold War to End of Time (1989-2023) - Mostofa, Shafi Md; Brasted, Howard (International Journal of Criminology and Sociology, 2023)
This paper discusses the impact of Covid-19 on Islamist narratives of end time scenarios that predict the annihilation of a corrupted world and its ultimate replacement by a world order based exclusively on Islam. It does this against the backdrop of Islam’s antagonistic relationship with the West, particularly from the ending of the Cold War in the early 1990s to the present day, a relationship conducted within the shadow of the US’s attempts to establish a new world order based exclusively on its own values and interests. In the light of the contrary predictions of Francis Fukuyama that the resulting Pax Americana will bring a century of peace and S. P. Huntington a century of conflict, the paper goes on to examine the vastly different world views of the United States on the one hand and Al Qaeda and Islamic State on the other and how they envisage the future unfolding. What the paper shows is that the advent of Covid-19 has served not only to convince traditional Islamic Scholars that Al Mahama, the great battle at the end of time, is well on the way and may even have started, but also to make Muslims in the streets more receptive to such a doomsday message.